Pengembangan Media Pembelajaran Android Pada Mata Pelajaran Informatika Untuk Siswa SMA Kelas X - Wirasasmita, Rasyid Hardi; Uska, Muhammad Zamroni; Kholisho, Yosi Nur; Ulfa, Delvia Samara; Hamdani, Fahri (Infotek: Jurnal Informatika dan Teknologi, 2025)
The learning media used in schools are still classified as conventional and have not utilised technology optimally. One solution that can be offered is the development of Android-based learning media as an innovative alternative in supporting the learning process. This research aims to develop Android-based informatics learning media, measure its feasibility level based on the assessment of media experts and material experts, and evaluate user responses. The method used is Research and Development (R&D) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study consisted of 27 class X students at SMAN 1 Sukamulia. The results showed that the learning media developed obtained a feasibility score of 90.7% from media experts and 90% from material experts, both of which were included in the very feasible category. Meanwhile, the user response to the application reached 94% with a very high category. These findings indicate that the developed Android-based learning media is not only feasible to use, but also receives positive acceptance from students. The academic contribution of this research lies in the development of digital media that is contextual and relevant to 21st century learning needs. Therefore, this media is recommended to be implemented more widely as well as being the basis for further development in the study of technology-based learning.